Comparative Analysis of Tidal Data from Forecasting Results with Measured Tide Data (Meneng Tidal Station Case Study) - Purna, Bagus Mustofa; Zakaria, Ahmad; Mariyanto, Mariyanto (Universitas Lampung, 2021)
AbstractThis research to find the similarity of the tidal characteristics of sea water, especially in the sea waters in the Meneng station area, where the data used is both hourly tide data from tide data from the website http: //tides.big.go.id and field measured tidal data for a period of 5 years, from 1988 to 1992 at the Meneng tidal station, East Java, Indonesia. The data used in this research have a minimum data length of 720 hours or 30 days, using 9 tidal harmonic components using the least squares method and then converted into the ANFOR program (Zakaria, 2005), this program can produce a periodic tidal data model. including the amplitude value that can be used to see a tidal characteristic of sea water. After the tidal data is modeled and analyzed, the correlation coefficient is generated. From the results of this study, it can be concluded that the component results obtained from the hourly tide data from the website http://tides.big.go.id and field measured data have something in common with the generated tidal components. The average correlation coefficient of the two data is 0.8010 and is included in the very good category. Keywords: tides, ANFOR, correlation coefficient